Regulatory gaps in the protection of the human rights of female live streaming hosts in platform-based employment relations - Fransiska Triwidya Purba (PT WIM Solusi Prima, 2026)
The rapid growth of the digital economy has generated new forms of platform-based employment, including the profession of live streaming hosts. This occupation has become increasingly popular among women due to its flexibility and accessibility as a source of income. However, the expansion of digital labor has not been accompanied by an adequate regulatory framework capable of ensuring the protection of workers' human rights, particularly those of women. This study aims to analyze the regulatory gap in the protection of women's human rights as live streaming hosts through a sociology of law perspective. The research employs an empirical legal method with a qualitative approach. Primary data were collected through semi-structured interviews with female live streaming hosts, while secondary data were obtained from laws and regulations, academic literature, and relevant supporting documents. The findings reveal significant regulatory gap s that hinder the fulfillment of fundamental labor rights, including access to social security, health protection, job security, and protection from digital violence and harassment. Furthermore, oversight mechanisms for digital platforms remain limited, resulting in an imbalance of bargaining power that places female workers in a vulnerable position. These findings demonstrate a discrepancy between law in books and law in action, which contributes to the structural exclusion of women within the digital economy. Therefore, regulatory reform and stronger policy measures grounded in a human rights approach are necessary to ensure fair, safe, and equitable working conditions for women in the evolving digital labor ecosystem.